Systematic Literature Review of Expert System - Mohamad Ilyas Abas; Deny Wiria Nugraha; Asminar Asminar; Isminarti Isminarti (TIN: Terapan Informatika Nusantara, 2023)
Current developments in technological science have had a major impact on our daily lives, one of the impacts is in the health and agricultural sectors which implement automated systems. This research aims to review current topics regarding expert systems and the use of some of the best algorithms used. The literature review was created by systematically reviewing 1000 research articles from the last 5 years (from 2016 to 2020) by collecting through related sources including conference proceedings and journals. The method used in this research is Systematic Literature Review (SLR). SLR is used to identify, study and interpret all relevant specific research. The results of this research reveal several algorithms that are frequently used and have good accuracy values ​​as well as trending topics in the field of expert systems.